Assessing Policy Impacts in Digital Services Trade: Implications for the Philippines - Neil Irwin S. Moreno; Francis Mark A. Quimba (Philippine Institute for Development Studies (PIDS), 2022)
Rapid digitalization has become an integral feature of the global economy in recent years, as markets became more connected and new modes of production and trade emerged. Having a relatively open digital environment, the Philippines is poised for digital trade integration with its Asia-Pacific neighbors. However, various measures must be taken for the country to be fully prepared for regional integration. Some of these are considered low-hanging fruits and can be quickly adopted by the government. This paper examined these low-hanging fruits, in terms of their effects on digital services trade. It conducted a two-stage regression of the gravity model of trade, using data from various sources. This allowed for the estimation of country-specific characteristics in the presence of three-way fixed effects. Results show that the low-hanging fruits generate heterogenous effects on digital services trade. Ratifying the revised WTO Agreement on Government Procurement (GPA) is positively associated with digital services trade, despite an earlier version having negative effects. Data retention requirements and online piracy have both positive and negative effects, while the effects of local loop unbundling were inconclusive. Overall, data retention was more facilitative while online piracy had greater adverse effects on digital services trade. These findings suggest the importance of acceding to the GPA, as well as revising the conditions of data retention requirements, strengthening copyright enforcement, and providing additional channels for promotion of legal content.
Keywords: 330; digital services trade; WTO GPA; local loop unbundling; data retention policy; copyright enforcement